A case report of infantile cystic nephroblastoma - Nozomu Kurose; Michiho Takenaka; Manabu Yamashita; Chie Shimaguchi; Mariko Nakano; Bryant Britni; Xin Guo; Chizuru Futatsuya; Akihiro Shioya; Sohsuke Yamada (BMC, 2018)
Abstract Background Nephroblastoma (NB) is a malignant embryonal neoplasm derived from nephrogenic blastemal cells. NB usually forms a solid mass, but in extremely rare cases, it may show cystic changes. Case presentation A six-month-old girl with persistent high fevers was found to have pyuria and bacteriuria. Ultrasonography revealed multilocular cysts in the right kidney. Right nephrectomy was performed with cyst wall rupture during surgery. An intraoperative rapid diagnosis, based on peritoneal fluid cytology, confirmed three components of blastemal, stromal, and epithelial cells. The blastemal cells were dyshesive, with scant to no cytoplasm and were the predominant cell type. The spindle-shaped stromal cells were arranged in fascicles. The epithelial cells demonstrated tubular structures. Macroscopically, the resected cystic tumor measured 80 mm in maximum diameter with a prominently thin cyst wall, but solid areas were also apparent. Histologically, the tumor was diagnosed as cystic NB (blastemal-predominant) displaying a triphasic pattern. Hyperchromatic nuclei and apoptotic bodies were found. The clinical stage classification of Japan Wilms Tumor Study group was 3. The patient was treated with chemotherapy and radiotherapy. Tumor recurrence and metastasis have not been observed in the 8 months since surgery. Conclusion This is an extremely rare case of infantile cystic NB. We diagnosed the NB cells that appeared in the peritoneal fluid by intraoperative rapid cytology. Cytological examination proved to be a very useful technique for determining the clinical stage of NB. Additionally, we propose that massive tumor degeneration and necrosis be considered as a pathogenic mechanism of cyst formation in NB.